Reduction of chronic hepatitis B‐related hepatocellular carcinoma with anti‐viral therapy, including low risk patients - Lin, D.; Yang, H.‐I.; Nguyen, N.; Hoang, J.; Kim, Y.; Vu, V.; Le, A.; Chaung, K.; Nguyen, V.; Trinh, H.; Li, J.; Zhang, J.; et al. (Alimentary pharmacology & therapeutics, 2016)
Summary Background Anti‐viral therapy in chronic hepatitis B (CHB) is associated with a reduced risk of hepatocellular carcinoma (HCC) primary described in patients with cirrhosis. Aim To examine the effects of treatment on HCC incidence in CHB with and without cirrhosis, after adjustment for background risks. Methods A total of 2255 CHB patients from a US cohort (973 received anti‐viral therapy) and 3653 patients from the community‐based Taiwanese REVEAL‐HBV study, none of whom received treatment. We used Cox proportional hazard models to calculate the risk of developing HCC after adjustment with the previously validated REACH‐B risk score. Results We found 273 incident cases of HCC. After adjustment, therapy lowered the risk of HCC development in the US treated cohort when compared to the US untreated cohort (HR 0.31; 95% CI: 0.15–0.66; P = 0.002). HCC risk reduction was also confirmed when compared to the REVEAL cohort (HR 0.22; 95% CI: 0.12–0.40; P < 0.001). Each REACH‐B point was associated with a 53% increased risk of HCC (HR 1.53; 95% CI 1.46–1.59; P < 0.001). We found a significant statistical reduction in HCC incidence with therapy regardless of gender, age, cirrhosis status, HBeAg serology, alanine aminotransferase level, REACH‐B score or treatment medication. Therapy was beneficial to those with mildly‐ to moderately elevated HBV DNA levels (>2000 IU/mL) and of even greater benefit to those with levels >200 000 IU/mL. Conclusion After adjustment for background risk, anti‐viral therapy was associated with a significant reduction in HCC incidence in both community and real‐life clinical cohorts, including in those patients previously thought to be at low risk.